Comparison of two alternative store formats using a Malmquist-type index - Vaz, Clara B. (2007)
This paper explores the differences in performance between two groups of retailing stores that operate with different formats. The study described in this paper combines the use of a Malmquist-type index (in a static setting) with statistical tests. This index is decomposed into sub-indexes for comparing the efficiency spread between groups and the productivity differences between the best-practice frontiers of the groups. The hypothesis tests are used to verify if the differences between groups captured by the Malmquist-type index and its components are statistically significant.